A Brief Study of Untouchable: Exploring the soul of Bakha in the face of untouchability (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Untouchable (l935) is a sociological novel which seeks to stress the evils of untouchability by focusing attention on the miserable plight suffering, poverty and degradation of a large section of Indian society. This evil has been high lightened by studying what happens to the soul of Bakha on a single eventful day. Sakha as an untouchable seeks his freedom in the infallibility of caste discrimi¬nation, with its hypocrisy, cruelty, deceit and inhumanity.